Specific and common functional connectivity deficits in drug-free generalized anxiety disorder and panic disorder: A data-driven analysis - Li, Wei; Cui, Huiru; Li, Hui; Colcombe, Stan; Smith, Robert C.; Cao, Xinyi; Pang, Jiaoyan; Hu, Qiang; Zhang, Lanlan; Yang, Zhi; Wang, Jijun; Li, Chunbo (Psychiatry research, 2023)
•Comparing anxiety disorder subtypes is essential for understanding the pathology.•gRAICAR reveals common and specific functional connectivity patterns across anxiety subtypes.•The pathological mechanism of PD could closely relate to the dysfunction of prefrontal cortex.•GAD could involve more extensive brain areas that are related to fear generalization. Evidence of comparing neural network differences between anxiety disorder subtypes is limited, while it is crucial to reveal the pathogenesis of anxiety disorders. The present study aimed to investigate specific and common resting-state functional connectivity (FC) networks in generalized anxiety disorder (GAD), panic disorder (PD), and healthy controls (HC). We employed the gRAICAR algorithm to decompose the resting-state fMRI into independent components and align the components across 61 subjects (22 GAD, 18 PD and 21 HC). The default mode network and precuneus network exhibited GAD-specific aberrance, the anterior default mode network showed atypicality specific to PD, and the right fronto-parietal network showed aberrance common to GAD and PD. Between GAD-specific networks, FC between bilateral dorsolateral prefrontal cortex (DLPFC) was positively correlated with interoceptive sensitivity. In the common network, altered FCs between DLPFC and angular gyrus, and between orbitofrontal cortex and precuneus, were positively correlated with anxiety severity and interoceptive sensitivity. The pathological mechanism of PD could closely relate to the dysfunction of prefrontal cortex, while GAD could involve more extensive brain areas, which may be related to fear generalization.